Notes on the “Pinocchio-cobweb-spider” Craspedisia cornuta (Keyserling, 1891) from southeastern of Brazil (Theridiidae, Pholcommatinae) - Brescovit, Antonio D.; Vasconcellos-Neto, João; Villanueva-Bonilla, German Antonio (Zootaxa, 2020)
Craspedisia cornuta (Keyserling, 1891), is redescribed on the basis of SEM data after more than fifty years after its last records. We also provide information on its natural history. SEM images for the proboscis, ventral plates of abdomen and male palp and epigynal plate are provided. Data on natural history using specimens collected in the Serra do Japi, from the state of São Paulo were analyzed and presented for the first time for this little-known species of Pholcommatinae theridiid spider.